Analisis Kelayakan Kawasan Ekonomi Khusus (KEK) Pariwisata dalam Meningkatkan Daya Tarik Investasi dan Perekonomian Lokal - Winanto, Sujoko; Ramdhan, Dadan (Institut Nalanda, 2024)
Tourism Special Economic Zones (SEZs) are strategic instruments for enhancing investment attractiveness and stimulating local economic growth. However, the effectiveness of Tourism SEZs in achieving these goals remains a subject of academic and policy debate. This study aims to analyze the feasibility of Tourism SEZs in boosting investment and regional economies through a literature review that examines economic theories, government policies, and case studies of existing SEZs. The research employs a qualitative approach based on a literature study from journals, books, and official reports. The findings indicate that the success of Tourism SEZs highly depends on factors such as investment incentives, supporting infrastructure, conducive regulations, and the active role of stakeholders. Additionally, SEZs with strong destination branding strategies tend to be more successful in attracting investment and increasing regional revenue. The study's implications highlight the importance of adaptive, data-driven policy design in managing Tourism SEZs to generate significant and sustainable economic impacts. Therefore, synergy between government, private sectors, and local communities is crucial in optimizing Tourism SEZs as a driver of local economic growth.